Kitab-Kitab Tafsir Dalam Pengajian Takmir Di Institusi Masjid Di Perlis: Kajian Tinjauan: Books of Tafsir in Takmir Studies in The Mosque Institutions in Perlis: A Review Study - Muhammad Lukman Mat Sin; Khalilullah Amin Ahmad (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
The mosque institutions are important platforms in the studies and dissemination of religious knowledge. They serve as the nucleus in producing civilized Muslim communities that are able to appreciate the Quran and sunnah in life. Takmir class is one of the forms of knowledge study in mosque institutions throughout the state of Perlis which also emphasizes the study of tafsir. Through the tafsir studies delivered by a certified takmir teacher, correct and accurate understanding of the meanings of al-Quran al-Karim can be achieved in moving towards the true appreciation of al-Quran al-Karim in life. Therefore, this article will describe the tafsir books used in the study of tafsir by reviewing five district mosques in Perlis and analyzing the opinions of mosque congregations who attended the related lectures. This study uses qualitative methods in the form of interviews, observations and document analysis. The researcher conducted interviews and observations on five selected informants among the takmir teachers who taught at the mosque, while document analysis was used by analyzing the materials or sources of turath writing that had been collected. Findings of the study show that the effectiveness of tafsir lectures at mosque institutions in Perlis are at positive levels in terms of the selection of tafsir books and their suitabilities with the mosque congregation and the congregation's response to the tafsir books taught. It is hoped that this study can instill interest in the community to deepen the meaning of al-Quran al-Karim which is the main source of legislation in Islam.